Biomotor Profile of Alte in the Pencak Silat PSHT Sports Branch, Ketawang Village, Gondang District, Nganjuk Regency in 2024 - Kahirulloh, Aldona; Kholis, Moh. Nur; Setiawan, Irwan (CV. Nusantara Sporta, 2024)
This study aims to evaluate the biomotor abilities of PSHT pencak silat athletes in Desa Ketawang, Kecamatan Gondang, Kabupaten Nganjuk. Initial observations indicated that female athletes exhibited weaknesses in speed, strength, agility, coordination, and endurance, leading to quick fatigue and suboptimal technical execution. The research employed a quantitative method with a series of tests, including a 60-meter sprint, push-ups, ball wall, wall squat, agility T-test, and a 1000-meter run. The results showed that 13.33% of the athletes were in the excellent category, 20% in good, 40% in fair, 20% in poor, and 6.67% in very poor. Overall, the biomotor profile of the athletes was categorized as fair. These findings suggest the need for more targeted training programs to enhance the biomotor abilities of the athletes, particularly in speed, strength, and endurance, to achieve optimal performance in pencak silat.